2014
DOI: 10.1016/j.geomorph.2014.03.051
|View full text |Cite
|
Sign up to set email alerts
|

Permafrost and snow monitoring at Rothera Point (Adelaide Island, Maritime Antarctica): Implications for rock weathering in cryotic conditions

Abstract: In February 2009 a new permafrost borehole was installed close to the British Antarctic Survey Station at Rothera Point, Adelaide Island (67.57195°S 68.12068°W). The borehole is situated at 31 m asl on a granodiorite knob with scattered lichen cover. The spatial variability of snow cover and of ground surface temperature (GST) is characterised through the monitoring of snow depth on 5 stakes positioned around the borehole and with thermistors placed at three different rock surfaces (A, B and C). The borehole t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…40 cm and a thermal offset of 0.8°C. The zero annual temperature depth is shallow and should be just below 4.5 m depth in contrast to other sites in the Western Antarctic Peninsula in high diffusivity bedrock settings (Ramos and Vieira, 2009;Bockheim et al, 2013;Guglielmin, et al, 2014). These characteristics are strongly influenced by the high porosity pyroclastic debris of Deception Island, which show a high ice-content at the base of the active layer.…”
Section: Discussionmentioning
confidence: 86%
“…40 cm and a thermal offset of 0.8°C. The zero annual temperature depth is shallow and should be just below 4.5 m depth in contrast to other sites in the Western Antarctic Peninsula in high diffusivity bedrock settings (Ramos and Vieira, 2009;Bockheim et al, 2013;Guglielmin, et al, 2014). These characteristics are strongly influenced by the high porosity pyroclastic debris of Deception Island, which show a high ice-content at the base of the active layer.…”
Section: Discussionmentioning
confidence: 86%
“…TDD g values calculated for JRI (496.1°C day in 2011–12 and 358.3°C day in 2012–13) are significantly higher than those for Livingston Island (98 to 257°C day; De Pablo et al ., ) and Signy Island (2 cm TDD g ranged between 260.5 and 378.0°C day for the period 2006–09; Guglielmin et al ., ). An even higher TDD g value of 618°C day has been recorded at Rothera Point, Adelaide Island (Guglielmin et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…A number of studies have suggested that the effect of air temperature on ground temperature is highly variable in the AP region (Cannone et al ., ; Guglielmin et al ., ). Whereas a relatively weak correlation (r = 0.58 to 0.82) between air and ground temperatures was reported from King George Island and Signy Island (Cannone et al ., ) in areas covered by different types of vegetation, a stronger relationship (r > 0.90) was described in areas of bare ground at Rothera Point (Guglielmin et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…() show the opposite tendency when compared to those of other locations with larger temperature amplitudes and similar mean annual ground surface temperatures (e.g. Guglielmin et al ., , ), which is hard to explain by differences in ground material properties. In fact, the surface thawing degree‐days are substantially lower on Amsler Island than at other sites within the Antarctic Peninsula (e.g.…”
Section: Climate Warming Explanation?mentioning
confidence: 99%
“…In fact, the surface thawing degree‐days are substantially lower on Amsler Island than at other sites within the Antarctic Peninsula (e.g. Guglielmin et al ., , ; Hrbáček et al ., ) or the northern hemisphere (e.g. Christiansen et al ., ), where thinner active layers have been reported.…”
Section: Climate Warming Explanation?mentioning
confidence: 99%